Destination Amyotrophic Lateral Sclerosis - Keon, Matt; Musrie, Benjamin; Dinger, Marcel; Brennan, Samuel E.; Santos, Jerran; Saksena, Nitin K. (Frontiers in Neurology, 2021)
Amyotrophic Lateral Sclerosis (ALS) is a prototypical neurodegenerative disease characterized by progressive degeneration of motor neurons both in the brain and spinal cord. The constantly evolving nature of ALS represents a fundamental dimension of individual differences that underlie this disorder, yet it involves multiple levels of functional entities that alternate in different directions and finally converge functionally to define ALS disease progression. ALS may start from a single entity and gradually becomes multifactorial. However, the functional convergence of these diverse entities in eventually defining ALS progression is poorly understood. Various hypotheses have been proposed without any consensus between the for-and-against schools of thought. The present review aims to capture explanatory hierarchy both in terms of hypotheses and mechanisms to provide better insights on how they functionally connect. We can then integrate them within a common functional frame of reference for a better understanding of ALS and defining future treatments and possible therapeutic strategies. Here, we provide a philosophical understanding of how early leads are crucial to understanding the endpoints in ALS, because invariably, all early symptomatic leads are underpinned by neurodegeneration at the cellular, molecular and genomic levels. Consolidation of these ideas could be applied to other neurodegenerative diseases (NDs) and guide further critical thinking to unveil their roadmap of destination ALS.